2017
DOI: 10.14814/phy2.13249
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of minced muscle graft progenitor cells to muscle fiber formation after volumetric muscle loss injury in wild‐type and immune deficient mice

Abstract: Volumetric muscle injury (VML) causes an irrecoverable loss of muscle fibers, persistent strength deficits, and chronic disability. A crucial challenge to VML injury and possible regeneration is the removal of all of the in situ native elements necessary for skeletal muscle regeneration. Our first goal was to establish a reliable VML model in the mouse tibialis anterior (TA) muscle. In adult male wild‐type and nude mice, a non‐repaired ≈20% VML injury to the TA muscle resulted in an ≈59% loss in nerve evoked m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 36 publications
(36 citation statements)
references
References 46 publications
5
31
0
Order By: Relevance
“…This response, however, was not found to be significantly different from either the 50% MG + HA group or our previously published benchmark for the delivery of 50% MG without accompanying scaffolding [ 13 ] suggesting neither the HA in isolation or the in combination with laminin-111 contributed significantly to whole muscle function beyond the effects of the supplied MG material. Moreover, while graft-mediated de novo muscle fiber regeneration was indicated by the presence of GFP + muscle fibers, as demonstrated previously [ 13 , 15 , 40 ], the robustness of the regenerative response was qualitatively in line with a recent observation of tissue equivalent (50% MG-only) implantation and was clearly lesser than a 100% MG repair [ 13 ].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…This response, however, was not found to be significantly different from either the 50% MG + HA group or our previously published benchmark for the delivery of 50% MG without accompanying scaffolding [ 13 ] suggesting neither the HA in isolation or the in combination with laminin-111 contributed significantly to whole muscle function beyond the effects of the supplied MG material. Moreover, while graft-mediated de novo muscle fiber regeneration was indicated by the presence of GFP + muscle fibers, as demonstrated previously [ 13 , 15 , 40 ], the robustness of the regenerative response was qualitatively in line with a recent observation of tissue equivalent (50% MG-only) implantation and was clearly lesser than a 100% MG repair [ 13 ].…”
Section: Discussionsupporting
confidence: 83%
“…GFP was detected in the defect region of the 50% MG + HA+LMN treated muscles at both 2 and 8 weeks post-injury indicating survival of the graft derived progenitor cells and their involvement in the myofiber regeneration ( Fig 5 ). Qualitative observation of GFP + staining indicated that the majority of the regenerated myofibers within the defect region were minced graft derived, as observed previously with minced graft-only repair [ 13 , 15 , 40 ].…”
Section: Resultssupporting
confidence: 74%
“…; Corona et al. ), it is difficult to rationalize that a relatively small loss of the TA muscle (~20%) in the current study ablates such a large portion of the satellite cell pool that cannot be compensated for by the bulk of the surrounding musculature (e.g., triceps surae muscles) that is left intact. Therefore, specific characteristics of this open fracture model points toward immune and autocrine/paracrine responses in nonrepaired and minced graft‐repaired VML injured muscles as potential primary mediators of fracture healing.…”
Section: Discussionmentioning
confidence: 64%
“…Mincing of the autologous tissue causes the adult fibers to die but delivers viable muscle progenitors and basal lamina required for de novo skeletal muscle regeneration [ 24 , 25 ] and induces a canonical muscle injury response that promotes fiber regeneration [ 26 ]. Devitalization and donor cell-labeling experiments indicate that minced grafts deliver muscle progenitors (e.g., satellite cells) that directly contribute to skeletal muscle fiber regeneration [ 19 , 27 29 ]. A significant shortcoming of the use of autologous muscle tissue is the obligatory donor tissue burden for the repair of clinically large VML defects.…”
Section: Introductionmentioning
confidence: 99%